Tinjauan Yuridis Pengawasan Keimigrasian Terhadap Imigran Ilegal Di Kota Pekanbaru - Nurainun '; Emilda Firdaus; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Refugee is a stranger who has no valid travel documents, Thus violating the provisions of Law Number 6 of 2011 on immigration. Further guidelines for refugees from other countries in Indonesia are not in accordance with the provisions of the law can be found in article 2 paragraph (1) The Director General of the Immigration Service Regulation Number IMI.1489.UM.08.05 of 2010 on the treatment of illegal immigrants is currently known in Indonesia imposed measures immigration. So that, Immigrants originating from these countries should be checked so that no things that are not desirable and feared can harm themselves and the local community. The research purpose of this dissertation, namely: First, to determine the immigration surveillance against illegal immigrants in Pekanbaru City. Second, to know what is the limiting factor in combating illegal immigrants in Pekanbaru City. Third, to find out what efforts can be made to keep an eye on illegal immigrants in Pekanbaru City.This type of research is a sociological or empirical research is the research in the field, This research was conducted at Immigration Office Class I Pekanbaru and RUDENIM Pekanbaru City. While the population and sample are all parties related to the problem studied in this study.The data sources used, the primary data, secondary data and data tertiary data collection techniques in this study were interviews, Questionnaire and literature study.The research has three key conclusions. First, Immigration control of legal immigrants in Pekanbaru City by the First Class Immigration Office of Pekanbaru has been under way, But the supervision of immigration in the field and the existence and activities of immigrants in the work area of the First Class Immigration Office of Pekanbaru still not effective. Second, The inhibiting factor in the supervision of illegal immigrants in Pekanbaru City is that there are internal factors and external factors. Third, Efforts that can be done to supervise illegal immigrants in Pekanbaru City such as forming a team of supervision and action of immigration, Forming an immigration security team, placing it into temporary shelter in immigration detention rooms and looking for translators. advies auteur, first, In order for the supervision to run, Then it can increase the quantity of Human Resources. Second, To UNHCR as an international patron who guarantees the honor of basic rights for refugees, Including the right as an asylum seeker to immediately follow up the illegal refugee status to Pekanbaru for immediate determination of its status or to deportation to a third country or to the country of origin of the immigrant if it is deemed safe. Third, Create checkpoints at certain locations and provide identifiers that are easily marked by the public that the foreigner is an illegal immigrant.Keywords: Control-Immigration-Illegal Immigrants